SOCIAL STRATIFICATION IN ROY’S THE GOD OF SMALL THINGS NOVEL (A SOCIOLOGICAL APPROACH) - Yosman, Arminsius; Surfaifel, Fety; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2025)
This study aimed to describe the forms of social stratification in Arundhati Roy’s novel The God of Small Things. The object of the study was the novel written by Arundhati Roy. The analysis focused on the depiction of social hierarchy and inequality among the characters in the story. The study applied a sociological approach using the theory by (Zahara & Anwar, 2021:24), which stated that there were three dimensions of social stratification in society: wealth (economic class), prestige (social status), and power. The research method used was descriptive qualitative, with data collected in the form of words, phrases, and sentences found in the novel. The results of the study showed that wealth was reflected through differences in the economic background of the characters, prestige was portrayed through caste position and family reputation, while power appeared in the form of authority, influence, and control exercised by certain characters over others. These three dimensions interacted to form a complex picture of social inequality that affected the relationships, lives, and conflicts of the characters in the novel. The findings emphasized that social stratification was not only a background element of the story but also a key factor driving the dynamics of conflict and the development of the plot in The God of Small Things.